ANALISIS KEPATUHAN RUMAH TANGGA TERHADAP INDIKATOR PHBS DI DESA GAMPONG TEUNGOH KECAMATAN SAWANG KABUPATEN ACEH UTARA - Ully Fitria; Mirna Yulia; Dian Rahayu; Wulan Mutia Permata; Serli Rahma Yuni; Maulidia (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
Clean and healthy living behavior (PHBS) is an important factor in improving the quality of public health and profiles of infectious and non-communicable diseases. Data on the prevalence of PHBS in Indonesia shows that despite the progress, there are still many families that have not fully applied the PHBS rate consistently. In the Northern Aceh Regent, especially in the village of Gampong Teungoh, in Sawang District, the spread of PHBS continues to show that there are challenges that require more attention. Efforts to improve PHBS are still underway at the rural level to achieve better health standards. The study aims to assess clean and healthy living behavior (PHBS) in households , which aims to empower family members and encourage their active role in the public health movement. This study uses a survey method with a questionnaire distribution involving 31 respondents from Gampong Teungoh Village. The results showed that the average level of compliance with the PHBS indicator was more than 70%, handwashing Indicators (85%), weight weight (78%) and use of clean water (82%), which shows high compliance. However, there are challenges in keeping healthy latrines at 62% and high smoking habits, about 40% of respondents, who smoke. Factors influencing PHBS include education, income, access to medical facilities, and socialization/education of PHBS. In conclusion, although the level of compliance of PHBS in Gampong Teungoh Village is quite high, there are still challenges that need to be overcome, especially related to healthy latrines and smoking habits. Efforts to overcome this challenge can be made to ensure increased access to healthcare facilities, more intensive education and smoking Through anti-campaign campaigns. Based on the results of the study, it is recommended that the government and related parties strengthen the socialization of PHBS through more intensive campaigns, as well as increase In addition, more attention should be paid to smoking prevention and improving healthy latrine facilitiesAll in the family. Further education about the importance of PHBS, especially for housewives, is urgently needed to create a better change in behavior to support family health.